SecKit: A Model-based Security Toolkit for the Internet of Things. Issue 54 (October 2015) - Neisse, Ricardo; Steri, Gary; Fovino, Igor Nai; Baldini, Gianmarco
Abstract: The control and protection of user data is a very important aspect in the design and deployment of the Internet of Things (IoT). The heterogeneity of IoT technologies, the large number of devices and systems, and the different types of users and roles create important challenges in this context. In particular, requirements of scalability, interoperability, trust and privacy are difficult to address even with the considerable amount of existing work both in the research and standardization community. In this paper we propose a Model-based Security Toolkit, which is integrated in a management framework for IoT devices, and supports specification and efficient evaluation of security policies to enable the protection of user data. Our framework is applied to a Smart City scenario in order to demonstrate its feasibility and performance.